Chronic Alcohol Ingestion Changes the Landscape of the Alveolar Epithelium. (30th December 2012) - Downs, Charles A.; Trac, David; Brewer, Elizabeth M.; Brown, Lou Ann; Helms, My N.
Abstract : Similar to effects of alcohol on the heart, liver, and brain, the effects of ethanol (EtOH) on lung injury are preventable. Unlike other vital organ systems, however, the lethal effects of alcohol on the lung are underappreciated, perhaps because there are no signs of overt pulmonary disorder until a secondary insult, such as a bacterial infection or injury, occurs in the lung. This paper provides overview of the complex changes in the alveolar environment known to occur following both chronic and acute alcohol exposures. Contemporary animal and cell culture models for alcohol-induced lung dysfunction are discussed, with emphasis on the effect of alcohol on transepithelial transport processes, namely, epithelial sodium channel activity (ENaC). The cascading effect of tissue and phagocytic Nadph oxidase (Nox) may be triggered by ethanol exposure, and as such, alcohol ingestion and exposure lead to a prooxidative environment; thus impacting alveolar macrophage (AM) function and oxidative stress. A better understanding of how alcohol changes the landscape of the alveolar epithelium can lead to improvements in treating acute respiratory distress syndrome (ARDS) for which hospitalized alcoholics are at an increased risk.